Evaluation of the efficacy of platelet-rich plasma in the treatment of training-induced knee traumatic osteoarthritis: a retrospective study based on a multidimensional quantitative evaluation - Cheng, Chao; He, Yongzhi; Wang, Huage; Xiao, Zhonglin; Wang, Linjie; Pang, Rizhao; Zhu, Li; Wang, Zhengdong; Zheng, Jinqi; Wang, Wenchun; Huang, Shiyu (Frontiers in Musculoskeletal Disorders, 2025)
ObjectiveIn this study, we retrospectively evaluated the efficacy of platelet-rich plasma (PRP) for the treatment of training-induced knee traumatic osteoarthritis (KTOA) by means of a functional scale and MRI cartilage score, and analysed its effects on the improvement of knee function, pain relief and cartilage repair.MethodsIn this study, 120 patients with training-induced KTOA (screened from 519 cases) were retrospectively analysed from May 2019 to December 2023, and knee function, pain and cartilage repair were evaluated by LKSS, VAS and MRI cartilage scores before and 3 months after treatment, and the statistical methods used were paired t-tests or Wilcoxon tests (P < 0.05).ResultsAmong 120 patients with training-induced KTOA treated with PRP, the Lysholm Knee Score (LKSS) significantly improved from (62.34 ± 18.69) to (81.2 ± 18.20) at 3 months after treatment, and the effective rate was 55.0%; the visual analogue score (VAS) of pain decreased from (5.24 ± 1.57) to (2.66 ± 1.43), and the effective rate of 81.7%; MRI cartilage damage score decreased from (3.24 ± 0.72) to (3.02 ± 0.86), and the effective rate was 36.7%; the differences were statistically significant (P < 0.05).ConclusionKTOA due to PRP therapeutic training improves joint pain and promotes the recovery of knee joint function. Meanwhile, it has a repairing effect on articular cartilage damage.